2006
DOI: 10.15560/2.3.30
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of polychaete species from Paraná state (Southern Brazil)

Abstract: A checklist of polychaete species recorded from Paraná State (Southern Brazil, 25°10’– 25°58’ S / 47°59’– 48°35’ W), including estuarine areas from Paranaguá and Guaratuba Bays and shallow continental shelf bottoms, is reported. Altogether 44 families, 164 genera, and 259 valid species are currently known from the area. The list, which provides a synthesis of the regional taxonomical work carried out until now, can serve as a baseline survey for future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
1
16
0
2
Order By: Relevance
“…Species with uni-, bi-or tridentate hooks should be included within the subgenus Scolelepis Blainville, 1828, whereas those with multidentate hooks are included within Parascolelepis Maciolek, 1987. This division into two subgenera has been adopted by several authors (e.g., BLAKE 1996, DELGADO-BLAS 2006, DELGADO-BLAS et al 2009 Orensanz & Gianuca, 1974; Parascolelepis texana Foster, 1971(AMARAL et al 2012) and P. quinquedentata Hartmann Schröder, 1965(LANA et al 2006. The overlap of characteristics among different species, and the great variability within and among populations have lead to difficulties in species diagnostics, increasing the risk of misidentification.…”
mentioning
confidence: 99%
“…Species with uni-, bi-or tridentate hooks should be included within the subgenus Scolelepis Blainville, 1828, whereas those with multidentate hooks are included within Parascolelepis Maciolek, 1987. This division into two subgenera has been adopted by several authors (e.g., BLAKE 1996, DELGADO-BLAS 2006, DELGADO-BLAS et al 2009 Orensanz & Gianuca, 1974; Parascolelepis texana Foster, 1971(AMARAL et al 2012) and P. quinquedentata Hartmann Schröder, 1965(LANA et al 2006. The overlap of characteristics among different species, and the great variability within and among populations have lead to difficulties in species diagnostics, increasing the risk of misidentification.…”
mentioning
confidence: 99%
“…Regarding the occurrence of species, recent literature was checked and data were compared with records provided for Patos Lagoon (Bemvenuti et al 2005), the states of Santa Catarina (Almeida et al 2012) and Paraná (Lana et al 2006), São Sebastião Channel (Pires-Vanin et al 2014), São Paulo continental shelf (Paiva 1993), Guanabara Bay (Santi and Tavares 2009) and Vitória Bay Estuarine System (Nalesso et al 2005). All taxa that occurred in this study were previously found in those regions.…”
Section: Discussionmentioning
confidence: 90%
“…It occurs in several geographic areas in the world. Not only was it reported in close areas in southern Brazil (LANA et al, 2006), but also in other regions in Southwestern Atlantic, more precisely in Argentina (ELÍAS et al, 2006;BREMEC;GILBERTO, 2006), in North Carolina (HYLAND et al, 2004) and California (SWAN, et al, 2007) in North America, and in further places such as the Mediterranean Sea (ERGEN, et al 2006). In these places it has been reported as inhabiting low salinity waters (in estuaries) and this fact seems also to be true to other supposed close relatives, as Neanthes japonica Izuka, 1908(LIU 2009 Even though N. fluviatilis and A. succinea are known to occur in areas of lower salinity, the present paper is the first formal record of these two polychaete species in Faisqueira River, in Paranaguá Bay, southern Brazil.…”
Section: The Nephtyid Polychaete Nephtys Fluviatilismentioning
confidence: 99%